Youth Awareness of Facebook Users’ Data Commodification and its Business Model - Abigail Boima; Toks Oyedemi (Communicare)
Facebook (Meta) is one of the world’s richest corporations, with about 98% of its revenue generated from advertising. Beyond its utilitarian function of connecting billions of people, Facebook is a global advertising machine that basically functions by commodifying users’ information and monetising their behavioural data. But are users aware of this? While studies have examined youth’s awareness of risks in online engagements, there are limited studies on youth’s awareness of the commodification of their information and target advertising directed at them as a trade-off for ‘free’ access to online platforms. This study investigated if educated youth with Facebook accounts in South Africa were aware of this commodification process and that Facebook uses their information for advertising revenue. Drawing theoretically from discourses on commodification and digital capitalism, we examined youth’s media literacy awareness about Facebook’s commercial operation. We conducted a survey of 103 university students and employed online ethnography to elicit responses from a community of university students. The online ethnography generated 24 comments. Findings showed that the majority of participants were unaware of this basic critical media literacy fact about the commercial operations of Facebook. This inspired the recommendation for a broader focus on critical media literacy for youth, whose sociability and sense of citizenship are increasingly shaped by engagements on digital platforms.